Omens of Adversity : Tragedy, Time, Memory, Justice - Scott, David, 1958- (Book collections on Project MUSE., 2014)
Omens of Adversity is a profound critique of postcolonial temporality. David Scott argues that the palpable sense of the present as time stalled, without hope for emancipatory futures, has had far-reaching effects on how we think about justice and the nature of political action.